FORMULATION OF MINERBA LAW ENFORCEMENT POLICY AGAINST UNCONVENTIONAL MINE FLOATING CATEGORY (STUDY OF SOCIO LEGAL IN BANGKA DISTRICT) - rahayu, derita prapti; YOKOTANI, YOKOTANI; Toni, Toni (JOURNAL OF PRIVATE AND COMMERCIAL LAW, 2018)
The floating TI problem will also have an impact on policies on environmental conservation, fisheries and cultural change. Subjectivity of policy issues.  This research approach is socio-legal. Research with such an approach, views the law in its complex face, not only stops at the norm, but also targets how the process of formation is up to its implementation. TI floating problems must be identified related to issues of authority, economic and environmental issues. With this concept, this research was carried out by conducting a step review of norms for the first stage. In the next stage, a search for certain norms related to floating TI is carried out the act of number 4 ‘ 2009 on Minerals and Coal. It was only analyzed by offering how floating law enforcement related to IT in the Bangka Regency area. Policy problems are only possible when humans make judgments about the desire to change some problem situations. The policy problem is the result / product of human subjective assessment, the policy problem can also be accepted as legitimate definitions of objective social conditions and hence policy problems are understood, maintained and changed socially; and there are many solutions to a problem as there are many definitions of the problem. Problems and solutions are in constant changes.